Analisis Kesalahan Siswa dalam Menyelesaikan Soal Bangun Ruang Sisi Lengkung Menggunakan Prosedur Newman - Adilah, Nihadhu; Sari, Nurul Husnah Mustika (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Many students of SMP N 1 Kajen have difficulty in solving mathematical story problems, especially those related to curved-sided geometric shapes. This research aims to find and analyze the types of errors made by students when solving curved geometric shape story problems. This research uses a qualitative descriptive method with data from test questions and student interviews. The results of the study showed that students made various types of errors in solving curved sided geometric story problems. These errors are categorized into four. Misunderstanding: students do not understand the concept or information given in the question. Transformation errors: students are unable to translate problem information into the appropriate mathematical form. Process skills errors: students make errors in carrying out calculations or mathematical operations. Final answer writing error: the student did not write the answer correctly or completely.